Comparison of Drying Shrinkage of Concrete Specimens Recycled Heavyweight Waste Glass and Steel Slag as Aggregate - Choi, So Yeong (Materials (Basel), 2020)
This study analyzed the fundamental properties of concrete using steel slag, to test its viability as an aggregate material. An experimental investigation into the effect of steel slag as a coarse aggregate, and heavyweight waste glass as a fine aggregate, on the drying shrinkage of concrete was performed. The calculated shrinkage strain was compared to five different shrinkage prediction models, namely, the ACI 209, B3, KCI 2012, EC 2 and GL 2000 model codes, to evaluate their ability to accurately predict shrinkage behavior. From the results, the elastic modulus of concrete increased with the increase in steel slag substitution ratio, however drying shrinkage decreased. The predictive value of the existing prediction model of drying shrinkage differed from the experimental values, and requires correction to improve its accuracy. The B3 model code showed the best prediction results of drying shrinkage.